2019
DOI: 10.1177/0040517519838068
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of factors affecting the seam slippage of garments

Abstract: Seam slippage often occurs with some garments during the process of wearing or washing, which not only affects the appearance of the garment but also influences garment quality. The purpose of this study is to find out the factors that affect the seam slippage of garments. In order to make the test results closer to those of the garment itself, this study first proposed to make the fabric into a Japanese woman's prototype sample, in order to simulate the garments produced by a garment enterprise. Then, accordi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 22 publications
(17 reference statements)
1
11
0
Order By: Relevance
“…Seam slippage is also dependent on the sewing direction. Seam slippage in the weft direction is higher and with the increase of the angle between the weft yarn and the sewing direction, seam slippage decreases (Pasayev et al, 2012;Ozdemir and Yavuzkasap, 2012;Mukhopadhyay and Midha, 2013;Namiranian et al, 2014;Chen and Cheng, 2019). This probably results from the fact the warp density is higher than the weft density.…”
Section: Parameters Affecting Seam Qualitymentioning
confidence: 98%
See 3 more Smart Citations
“…Seam slippage is also dependent on the sewing direction. Seam slippage in the weft direction is higher and with the increase of the angle between the weft yarn and the sewing direction, seam slippage decreases (Pasayev et al, 2012;Ozdemir and Yavuzkasap, 2012;Mukhopadhyay and Midha, 2013;Namiranian et al, 2014;Chen and Cheng, 2019). This probably results from the fact the warp density is higher than the weft density.…”
Section: Parameters Affecting Seam Qualitymentioning
confidence: 98%
“…Gurarda (2008) stated that there was no significant effect of ticket number in both the warp and weft direction seam slippage strength of the fabrics. Vice versa, according to the experimental results of Chen and Cheng (2019), the larger the sewing thread linear density of polyester material is, the smaller the seam slippage. Behera and Chand (1997) stated that the seam efficiency of the lightest fabric invariably increases with the increase in the ticket number of the sewing threads irrespective of their composition.…”
Section: Parameters Affecting Seam Qualitymentioning
confidence: 99%
See 2 more Smart Citations
“…The unique "skin core" structure of the fiber brought excellent flame retardant performance, and had the moisture absorption, ventilation and comfort of cellulose fiber suitability. [1] Professor Liu of University of science and technology of China synthesized a kind of phosphite modified chitosan (PCS) flame retardant, and deposited the films of PCS and branched polyvinylamine on the polyester cotton blend via layer-by-layer self-assembly technology, so as to prepare polyester fabric with flame retardant property. It was found that the thermal stability of this kind of fabric was enhanced.…”
Section: Flame Retardant Protectionmentioning
confidence: 99%